Awareness and barriers to accessing sexual and reproductive healthcare services among Deaf women in Krachi West District of Ghana: a qualitative study - John Kwame Agbenyeavu; Gilbert Eshun; Richard Gyan Aboagye; John Kuumuori Ganle (Reproductive Health)
Abstract Background Although Ghana is one of the countries that has ratified the United Nations Convention on the Rights of Persons with Disabilities and enacted the Persons with Disabilities Act, women with disabilities across the country have continuously reported barriers to accessing sexual and reproductive healthcare services. Such barriers hinder the achievement of the United Nations Sustainable Development Goals 3 and 10, which aim to promote good health and well-being and reduce inequalities within and among countries, respectively. This study explored the awareness of sexual and reproductive healthcare (SRH) services and barriers to accessing them among Deaf women in the Krachi West District. Methods This study employed a descriptive qualitative design, using in-depth interviews as the main data collection technique. Our study spanned from November 2021 to January 2022, and it included 13 Deaf women aged 15 to 49 in the Krachi West District of Ghana. The participants were selected using the purposive sampling method. Thematic content analysis was employed for data analysis, with QSR NVivo 12 software used for coding and developing themes. Results All participants were aware of SRH services such as family planning, antenatal care, and postnatal services, with family members and partners being their primary sources of information. The study identified several key barriers to accessing these services, including financial constraints, high service costs, communication difficulties with healthcare providers, stigma, inappropriate attitudes from healthcare providers, and a lack of community support. Conclusion The study found that all participants were aware of SRH services, although few made use of them. Socio-economic, health system, and community-level barriers, such as an inability to pay, communication gaps, negative attitudes from healthcare workers, and a lack of community support, hinder Deaf women from accessing SRH services. Our findings call for reorienting the health system to accommodate the SRH needs of women with hearing disabilities. Additionally, public education and sensitisation are needed to improve people’s understanding of the SRH needs of persons with disabilities, such as Deaf women, and the importance of supporting their needs with the available resources.